Improving The Recipe and Technology of Wheat Bread Using Apple Pomace (Global Scientific Review, 2024)
The influence of apple raw materials (powder from apple pomace and frozen apple pomace) on the duration of individual operations of the technological process of the straight method of producing wheat bread was studied: the duration of kneading, the number of kneadings, the duration of the dough fermentation process and proofing of dough pieces. As studies have shown, when using recycled apple raw materials in the production of wheat bread, the amount of yeast must be increased to 3-4%, in contrast to the 1-2% introduced in the control sample.